Improving workplace safety through safety awareness training at PT Barata Indonesia - Fitri Sulistyo Budi (Nur Science Institute, 2025)
Workplace safety remains a crucial concern in Indonesia's industrial sector. According to BPJS Ketenagakerjaan, more than 315,000 occupational accidents were recorded in 2023, with 73% occurring in the manufacturing and construction sectors. This alarming number highlights the need for psychological and behavioral interventions rather than technical compliance alone. This study aims to examine how Safety Awareness Training at PT Barata Indonesia can improve employees' cognitive, emotional, and behavioral awareness toward safe practices. Using a pre–post test design involving 400 participants, the training program focused on risk perception, motivation, and safety-related self-efficacy. Results showed a significant improvement in participants' knowledge and engagement, with a 30% increase in post-test scores. Findings emphasize the role of psychological mechanisms such as motivation, reinforcement, and observational learning in developing a safety-oriented mindset. This study contributes to understanding how structured psychological interventions can create long-term behavioral change in workplace safety.